The Critical Role of Bach2 in Shaping the Balance between CD4+ T Cell Subsets in Immune-Mediated Diseases - Lingyi Yang; Shuli Chen; Qiuyu Zhao; Ying Sun; Hong Nie (Mediators of Inflammation)
The transcription factor Bach2 which is predominantly expressed in B and T lymphocytes represses the expression of genes by forming heterodimers with small Maf and Batf proteins and binding to the corresponding sequence on the DNA. In this way, Bach2 serves as a highly conserved repressor which controls the terminal differentiation and maturation of both B and T lymphocytes. It is required for class switch recombination (CSR) and somatic hypermutation (SHM) of immunoglobulin genes in activated B cells, and its function in B cell differentiation has been well-described. Furthermore, emerging data show that Bach2 regulates transcriptional activity in T cells at super enhancers or regions of high transcriptional activity, thus stabilizing immunoregulatory capacity and maintaining T cell homeostasis. Bach2 is also critical for the formation and function of CD4+ T cell lineages (Th1, Th2, Th9, Th17, T follicular helper (Tfh), and regulatory T (Treg) cells). Genetic variations within Bach2 locus are associated with numerous immune-mediated diseases including multiple sclerosis (MS), rheumatoid arthritis (RA), chronic pancreatitis (CP), type 2 chronic airway inflammation, inflammatory bowel disease (IBD), and type 1 diabetes. Here, we reveal a critical role of Bach2 in regulating T cell biology and the correlation with these immune-mediated diseases.